Analysis of infrared spectroscopy absorption characteristics of graphene transferred to grating structures. (October 2020) - Pan, QingHui; Guo, YanMing; Zhou, SiHong; Shuai, Yong; Tan, HePing
Highlights: A graphene transferred to Au/SiO2 /Au grating structure is designed and fabricated. We have experimentally demonstrated high absorption in six sets of graphene grating devices in the infrared region. We deeply analyzed the differences between the experimental and simulation of the dynamic control characteristics of graphene grating structures. Abstract: In this paper, we designed and fabricated a graphene transferred to grating structure with high absorption from 4 µm to 14 µm. The grating structure was composed of Au/SiO2 /Au and the graphene was grown by chemical vapor deposition (CVD) in vacuum conditions. We have experimentally demonstrated that magnetic polaritons (MPs) and graphene plasmon were excited to achieve high absorption in six sets of graphene grating devices in the infrared region, which were in good agreement with the simulation results. We also discuss the effect of controlling the Fermi level of graphene on the absorption spectrum of the device. The research method can provide potential support for the application of graphene in infrared optoelectronics.